Singaporeans' perceptions on foreign talent - Lee, Fei Fei (2008)
Through the study, we found out that Singaporeans are generally receptive towards the bringing in of foreign talent to our country to augment the local talent pool.According to the respondents, foreign talent is most needed in 3 areas, namely Information Technology, Scientific Research, and Arts/Culture.